Applying Hindu Religious Principles in Elementary School Learning - Suranti, Ni Made Yeni; Pradmawati, Ni Ketut Yeni (Indonesian Journal of Teacher Education, 2025)
Hindu religious education plays a strategic role in shaping the character of elementary school students through the internalization of religious values. This article aims to examine the application of Hindu religious teachings in elementary school learning as a means of strengthening character education. The research method used was a literature review, analyzing various sources, including books, journal articles, and relevant research findings. The results of the study indicate that the application of the teachings of Tri Kaya Parisudha, Catur Guru, Tat Twam Asi, Tri Hita Karana, and Karma Phala in Hindu religious learning contributes significantly to shaping students' attitudes, behaviors, and personalities. These five teachings guide students in thinking, speaking, and acting in accordance with moral, spiritual, social, and personal responsibility values. Therefore, the integration of Hindu religious teachings into elementary school learning serves as an important foundation for the holistic development of students' character.